Analysis and Ranking of Factors Affecting Resilient Supply Chain with a Combined Approach - Zamen, Shirin; Haghighat Monfared, Jalal; Keramati, Mohamad Ali (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: Today, there is increasing competition among various organizations, and one of the competitive tools is supply chain management. Existing pressures and disruptions for companies have led to working under uncertain conditions. Therefore, the supply chain must be made resilient. Such a chain is of great importance in the oil industry, which is one of the country's most essential activities. Accordingly, this study seeks to identify and prioritize the factors affecting a resilient supply chain in the oil industry.Methodology: This research was conducted in one of the active companies in the oil industry. Initially, semi-structured interviews were conducted with 10 experts from the company, who were purposefully selected, and analyzed using the thematic analysis technique.Findings: This analysis identified 13 factors. In the next step, using the Best-Worst Method (BWM), these factors were ranked, with financial factors, flexibility, the use of experienced managers, the use of backup suppliers, and foresight being ranked first to fifth, respectively.Conclusion: Overall, it is recommended to focus on these underlying factors as the foundation of supply chain resilience.